Review: Isolation of Gelatin from Several Types of Fish - Suryaman, Ine Suharyani; Sulastri, Lela; Astuti, Enih Nindi; Delviyanti, Elis; Senja, Rima Yulia; Tomi, Tomi (Universitas Padjadjaran (Unpad), 2025)
Indonesia is a country with the largest fishery waste, one of which is fish bones as a source of gelatin. Gelatin is the main protein that makes up skin and bone tissue in animals. This review was compiled to compare the results of isolating gelatin from bone waste in various types of fish. Articles were collected from the website https://scholar.google.co.id/ with